TEACHING STRATEGIES IN SWIMMING AND AQUATICS - Lyndon Bailon (Tạp chí Khoa học Đại học Đà Lạt)
Research-based instructional materials, such as course manuals, should be used to optimize the performance of instructors teaching swimming and aquatics. This study used an exploratory research design to explore the teaching strategies and challenges of ten swimming and aquatic course instructors at Bicol University through survey interviews and curriculum analysis. The study revealed that the instructors used various teaching approaches in the course, depending on the topic. Major challenges were poor facilities, overcrowded pools, and a lack of professional development. A course manual covering the eight topics of the course was developed. The manual was evaluated and scored as acceptable for use in teaching the course. It was concluded that the techniques for implementing theory-based learning and the difficulties that educators face may serve as the foundation for the development of successful teaching resources, such as books and manuals. Strong institutional support for providing adequate facilities and professional development for instructors is recommended. Use of the manual developed here is encouraged to evaluate its effectiveness.